The Effect Of The New Normal Regulations Of The Covid-19 Pandemic On The Visist Of Patients Dental And Mouth - Tarianna Ginting; Putri Yunita Pane; Dameria Dameria; Efendi S Nainggolan; Suermawati Suermawati (CV. Inara, 2022)
Covid-19 cases in Indonesia are increasing every day. This situation has an impact on people's lives, especially in the economic field due to social restrictions that occur in the community. Therefore, the government has started to gradually reopen social restrictions to save the economy. This initiative is known as